PERBANDINGAN ETIKA IMMANUEL KANT DAN JOSEPH FLETCHER SERTA RELEVANSINYA TERHADAP POSITIVISME HUKUM DI INDONESIA - Winarso, Kornelius Ayub Dwi (Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2020)
AbstractThis paper focuses on discussing the issue of legal positivism in Indonesia. As is known to the public, rigorous law enforcement has become a familiar phenomenon in the community. The law is applied rigidly and indiscriminately. As a consequence, many small people become victims of the